STRATEGI KOMUNIKASI DEWAN PIMPINAN DAERAH PARTAI PERSATUAN INDONESIA (DPD PARTAI PERINDO) DALAM MELAKUKAN PENCITRAAN DI KOTA PEKANBARU - Regina Emsi; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Partai Persatuan Indonesia (Partai PERINDO) is a newly established political party and has never participated as a participant in the general elections held in Indonesia. The establishment of the Indonesian Persatuan Party (PERINDO Party) started with the establishment of the Association of Indonesian Unity Society (ORMAS PERINDO) officially established on February 23, 2013. Approximately 2 years after the founding of the Persatuan Indonesia Society (ORMAS PERINDO), on February 7, 2015 Persatuan Indonesia (Partai PERINDO) is officially established. The Regional Council of the Partai Persatuan Indonesia (DPD PERINDO Party) Pekanbaru Town which is structurally at the district / city level should not only wait for the communication strategy conducted by the Central Executive Board of the Partai Persatuan Indonesia (DPP PERINDO Party) in the image of Partai Persatuan Indonesia PERINDO) to gain sympathy in the midst of society. The formulation of this research problem, how is the communication strategy of the Regional Leadership Council of the United Indonesia Party (DPD Party PERINDO) in imaging in Pekanbaru City? ". The purpose of this research is to know the communication strategy of Regional Leadership Council of Indonesian Persatuan Party (DPD Party PERINDO) in imaging in Pekanbaru City, and to know the factors that support and obstruct the Regional Leadership Council of Indonesian Persatuan Party (DPD Party PERINDO) in Pekanbaru City. Qualitative research methods. Research location of Regional Leadership Council of United Indonesia Party (DPD PERINDO Party) Pekanbaru City. Primary data sources through interviews as well as secondary data sources. Data analysis techniques were carried out by analysis of interactive analysis models of Miles and Huberman. The targets to be achieved in every activity held by the Regional Leadership Council of the Partai Persatuan Indonesia (DPD PERINDO Party) Pekanbaru City is to run and realize what is desired by members of the Persatuan Indonesia Party (PERINDO Party) in Pekanbaru City, and to get new members of the Party Persatuan Indonesia (Partai PERINDO) in Pekanbaru City. The Regional Leadership Council of Partai Persatuan Indonesia (DPD PERINDO Party) Pekanbaru City uses the means of communicating by holding activities that directly touch to the needs of the community in accordance with the vision and mission of the Persatuan Indonesia Party (PERINDO Party). Each activity begins with the opening of the event containing remarks from the representatives of the board, the government apparatus present, and the competent expert, about the communication strategy of message conveyor credibility. Audience as the recipient of the message from the audience strategy is the general public. The background of the audience knowledge, especially in the field of politics, most of which participate in knowledge activities is enough. This is influenced by the easier information obtained because of the availability of various media. The touch of audiences' feelings is an easy but difficult communication strategy. Selection of media using various activities. The following activities are: providing free ambulance facility, fogging, giving of Indonesian Union Party (PERINDO) selling cart shop for five-time traders, road hoarding, free medical treatment. The supporting factor is having its own secretariat or non-rental property right on Jl. Borobudur Pekanbaru City, and has its own ambulance so that whenever can be utilized. Inhibiting factors are funding conditions, human resource conditions, and archiving of activity documentation. Strategies are tactical, from ideas, planners, to execution of the program is a strategy. Badly connoted imagery is caused by the politician himself. The strategy undertaken by the Persatuan Indonesia Party (PERINDO Party) is the taking of momentum that there is good value then blow-up through the media. Indonesian society is very easy to sympathize to goodness regardless of who the person is and what he has made, so good visible then the perception is good, because that politics is perception.Keywords: communication strategy, imaging